Analysing the effects of strategic assets on company success : an evidence in manufacturing company - Samad, Sarminah; Abdullah Alsolami, Hazaz (International Journal of Engineering and Technology, 2018)
Manufacturing industry plays a significant role in the development of a nation. Thus, analyzing the factors influencing its success is profoundly needed. Scholars have identified strategic assets as a key factors that influence the success of manufacturing companies. This study examined the relationship between strategic assets on company success. 400 manufacturing companies in Malaysia have participated in the survey.Â  A total of 299 usable questionnaires were analyzed using Smart Partial Least Squares (PLS). The results revealed that manufacturing companies should consider increasing their strategic assets to achieve superior success. This suggests that strategic assets are crucial towards improving company success. The results found that intangible assets have emerged as the most significant predictor that affect company success. The implications of this study and recommendations for future research are also discussed.Â Â